Applications of Augmented Vision Head-Mounted Systems in Vision Rehabilitation - Peli, Eli (2007)
Vision loss typically affects either the wide peripheral vision (important for mobility), or central vision (important for seeing details). Traditional optical visual aids usually recover the lost visual function, but at a high cost for the remaining visual function. We have developed a novel concept of vision-multiplexing using augmented vision head-mounted display systems to address vision loss. Two applications are discussed in this paper. In the first, minified edge images from a head-mounted video camera are presented on a see-through display providing visual field expansion for people with peripheral vision loss, while still enabling the full resolution of the residual central vision to be maintained. The concept has been applied in daytime and nighttime devices. A series of studies suggested that the system could help with visual search, obstacle avoidance, and nighttime mobility. Subjects were positive in their ratings of device cosmetics and ergonomics. The second application is for people with central vision loss. Using an on-axis aligned camera and display system, central visibility is enhanced with 1:1 scale edge images, while still enabling the wide field of the unimpaired peripheral vision to be maintained. The registration error of the system was found to be low in laboratory testing.